Teaching and Implementation of the Hartree-Fock-Roothaan method for determining effective mass (2017)
One explanation of the phenomena associated to the behavior of electrons con- fined in a periodic lattice is proposed in this paper. The dynamics of the elec- trons can be determined more precisely using the mass effective approximation. We will carry this out using the Hartree-Fock-Roothaan method by emphasizing its usefulness in typical systems which requires this model for these calculations. An explanation and direct application of this method to a specific physics prob- lem is show in this paper.